Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

a. Use limits to find the derivative function [tex]f^{\prime}[/tex] for the function [tex]f[/tex].

b. Evaluate [tex]f^{\prime}(a)[/tex] for the given values of [tex]a[/tex].

[tex]f(x) = \frac{7}{2x + 1}; \, a = -\frac{1}{3}, \, 4[/tex]

a. [tex]f^{\prime}(x) = \square[/tex]


Sagot :

Sure, let's solve each part of the question step-by-step.

### Part a: Finding the Derivative Function [tex]\( f'(x) \)[/tex]

To find the derivative [tex]\( f'(x) \)[/tex] of the function [tex]\( f(x) = \frac{7}{2x+1} \)[/tex], we can use the limit definition of a derivative, but let's use standard differentiation rules for simplicity.

We have [tex]\( f(x) = \frac{7}{2x+1} \)[/tex]. This is a quotient, so we can use the chain rule to differentiate it. Let [tex]\( u = 2x + 1 \)[/tex]. Then:

[tex]\[ f(x) = \frac{7}{u} \][/tex]

To find [tex]\( \frac{d}{dx} \left( \frac{7}{u} \right) \)[/tex], we first find [tex]\( \frac{d}{du} \left( \frac{7}{u} \right) \)[/tex].

[tex]\[ \frac{d}{du} \left( \frac{7}{u} \right) = -\frac{7}{u^2} \][/tex]

Next, we need [tex]\( \frac{du}{dx} \)[/tex]:

[tex]\[ \frac{du}{dx} = 2 \][/tex]

Using the chain rule [tex]\( \frac{d}{dx} = \frac{d}{du} \cdot \frac{du}{dx} \)[/tex]:

[tex]\[ f'(x) = -\frac{7}{u^2} \cdot 2 = -\frac{14}{(2x+1)^2} \][/tex]

So, the derivative function is:

[tex]\[ f'(x) = -\frac{14}{(2x+1)^2} \][/tex]

### Part b: Evaluating [tex]\( f'(a) \)[/tex] for Given Values of [tex]\( a \)[/tex]

Let's now evaluate [tex]\( f'(a) \)[/tex] for [tex]\( a = -\frac{1}{3} \)[/tex] and [tex]\( a = 4 \)[/tex].

1. For [tex]\( a = -\frac{1}{3} \)[/tex]:

[tex]\[ f'\left( -\frac{1}{3} \right) = -\frac{14}{\left( 2 \left( -\frac{1}{3} \right) + 1 \right)^2} \][/tex]

Simplify the denominator:

[tex]\[ 2 \left( -\frac{1}{3} \right) = -\frac{2}{3} \][/tex]

[tex]\[ -\frac{2}{3} + 1 = -\frac{2}{3} + \frac{3}{3} = \frac{1}{3} \][/tex]

So:

[tex]\[ f'\left( -\frac{1}{3} \right) = -\frac{14}{\left( \frac{1}{3} \right)^2} = -\frac{14}{\frac{1}{9}} = -14 \cdot 9 = -126 \][/tex]

Therefore, [tex]\( f' \left( -\frac{1}{3} \right) = -126 \)[/tex].

2. For [tex]\( a = 4 \)[/tex]:

[tex]\[ f'(4) = -\frac{14}{(2 \cdot 4 + 1)^2} \][/tex]

Simplify the expression:

[tex]\[ 2 \cdot 4 + 1 = 8 + 1 = 9 \][/tex]

So:

[tex]\[ f'(4) = -\frac{14}{9^2} = -\frac{14}{81} \][/tex]

Therefore, [tex]\( f'(4) = -\frac{14}{81} \)[/tex].

### Summary

a. The derivative function [tex]\( f'(x) \)[/tex] is:

[tex]\[ f'(x) = -\frac{14}{(2x+1)^2} \][/tex]

b. Evaluating the derivative at the given points:

- [tex]\( f'\left( -\frac{1}{3} \right) = -126 \)[/tex]
- [tex]\( f'(4) = -\frac{14}{81} \)[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.